2017
DOI: 10.3390/molecules22122263
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Acanthamoeba castellanii Secretes the Extracellular Aminopeptidase M20/M25/M40 Family Protein to Target Cells for Phagocytosis by Disruption

Abstract: Acanthamoeba is free-living protist pathogen capable of causing a blinding keratitis and granulomatous encephalitis. However, the mechanisms of Acanthamoeba pathogenesis are still not clear. Here, our results show that cells co-cultured with pathogenic Acanthamoeba would be spherical and floated, even without contacting the protists. Then, the Acanthamoeba protists would contact and engulf these cells. In order to clarify the contact-independent pathogenesis mechanism in Acanthamoeba, we collected the Acantham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Huang and collaborators showed that proteins secreted by A. castellanii , induced the detachment of mammalian cells and assigned this effect to the M20/M25/M40 aminopeptidase superfamily proteins. These detached cells floated and were then ingested and killed by amoeba cells [ 84 ]. These proteins were not found in the EVs or EVs-free supernatant, but other molecules present in the secretome of A. castellanii could induce similar functions.…”
Section: Discussionmentioning
confidence: 99%
“…Huang and collaborators showed that proteins secreted by A. castellanii , induced the detachment of mammalian cells and assigned this effect to the M20/M25/M40 aminopeptidase superfamily proteins. These detached cells floated and were then ingested and killed by amoeba cells [ 84 ]. These proteins were not found in the EVs or EVs-free supernatant, but other molecules present in the secretome of A. castellanii could induce similar functions.…”
Section: Discussionmentioning
confidence: 99%
“…The matrix metalloproteases 2 and 7 of Bacillus cereus were cleaved with high efficiency at the Leu-Gly or Leu-Ala bond by the residue in the P1′ position [31]. A previous study showed that the M20/M25/M40 superfamily aminopeptidase protein, an aminopeptidase found in Asp can be hydrolyzed Leu-AMC more rapidly than Arg-AMC [24]. In this study, the results showed that Asp more rapidly hydrolyzed Leu-AMC than Arg-AMC, as well as the recombinant M28AP ( Figure 2B).…”
Section: Biochemical Characterization Of M28apmentioning
confidence: 99%
“…A previous study showed that the M20/M25/M40 superfamily aminopeptidase protein, an aminopeptidase that is found in Asp, causes cell line disruption after Acanthamoeba spp. and C6 cell co-culturing [24]. In general, the cell line causes organelle stress and induces apoptosis pathways due to parasite infection [35].…”
Section: Cell Line Apoptosis By M28apmentioning
confidence: 99%
See 2 more Smart Citations